Programa de qualidade na interação familiar (PQIF) no desenvolvimento das habilidades parentais. - Silva, Catarina de Santana (2023)
This research aimed to analyze the contributions of the Family Interaction Quality Program (FIQP) in the development of parenting skills among caregivers of children. Specifically, it sought to: contextualize the role of the family and family relationship dynamics, explore the concepts of parenting styles, parenting practices, parenting skills, and social cognitive theory; characterize the Family Interaction Quality Program; present the relevance of group intervention for caregivers of children; and reflect on the contributions of the program to the quality of family interaction. The study adopted a qualitative research-intervention approach, conducted synchronously online with caregivers of students from two schools in the metropolitan region of Recife: one from the private sector and the other from the public sector. In total, 31 caregivers of children aged 0 to 11 years participated in the study. The FIQP methodology was applied in four groups, consisting of 5, 7, 6, and 13 participants, respectively. Initially, an interview was conducted to form the groups, using the child's age and the relationship with the child as inclusion criteria. Before the intervention, a sociodemographic questionnaire was administered, along with the Parental Interaction Quality Scale (PIQS), both in the pre-test and post-test (after 3 months). The data collected were analyzed using thematic content analysis. The results revealed that the program operates preventively and promotes positive strategies. Several achievements were identified based on the caregivers' reports, such as the expansion of the participants' parenting skills repertoire, the recognition that caregivers serve as role models for their children, the creation of strategies to prevent behavioral problems in children, mediation in conflict resolution, and the formation of a network of mutual support and cooperation among caregivers. Additionally, there was a deeper understanding of behavioral principles, the development of rules, and the promotion of values, resulting in improvements in the quality of family interaction. This study aims to highlight the possibilities and potential of FIQP groups, as well as their contribution to the creation of training spaces for caregivers of children. The research emphasizes the importance of these programs as a means to strengthen caregivers' skills and improve the quality of family interaction.